Nilai-Nilai Pendidikan Akhlak dalam Al-Qur’an dan Relevansinya dalam Kehidupan Sehari-hari (Studi Analisis Kisah Qorun QS Al-Qashash Ayat 76-82) - Sri Maryati Bahtiar; Tajudin Noor; Abdul Kosim (FONDATIA, 2022)
Morals are an important element that must be owned by every Muslim person, but the decline in morality has an impact on today's era so that moral awareness and lack of knowledge about morality in everyday life decreases. So it requires a deep understanding of morality. Therefore, it is necessary to re-learn the important points about morality by studying them through exemplary stories that have been contained in the Qur'an. In the Qur'an QS. Al-Qashhash there is a story of Qarun from there we can see some lessons about morality and moral values contained in his story. This study aims to determine the moral values contained in QS. Al-Qashhash in the story of Qarun and to find out the important vocabulary contained in it, then study the relevance of moral values to human behavior in everyday life. The focus of this research refers to qualitative research methods and literature by taking primary data from the Qur'an and books of interpretation along with other explanations with hadiths and books related to the discussion of morality and the story of Qarun. To analyze the data, this research explains it through the method of tahlili interpretation and interpretation of the vocabulary contained in the Qur'an. The results obtained by this study are, knowing the important vocabulary about moral education contained in the treasure story in QS. Al-Qashhash, then we can understand what moral values are contained in the story of Qarun in order to understand moral education and then from there we can see its relevance to human behavior in everyday life.